Sky-wave over-the-horizon radar simulation tool - Saavedra, Zenon (2020)
This work deals with the entire process of target detection and ranging by a sky-wave over-the-horizon radar (OTHR) computational model simulation. The different processing stages of the transmitted signal along its space-time trajectory from transmission to digital signal processing are modelled. With this simulation tool a moving target present over the sea can be detected according to a set of given initial conditions together with the ionosphere model inputs and the target electromagnetic model. Initial conditions as well as the modulation and filtering options among other parameters of the model can be set easily. The present work is intended to be a further contribution to OTHR studies, providing a user-friendly tool of easy application in order to improve a radar design, facilitate its implementation, as well as for debugging algorithms and signal processing techniques.